Agricultural seed production / (Acc. 5106) - George, Raymond A. T. (Wallingford, Oxfordshire ; Cambridge, MA : CABI, 2011)
A practical coverage of the principles of producing seeds for the main agricultural crops, this book emphasises producing optimal quality seed, and applies to small and large scale farms worldwide. Cereals such as wheats, rice, barley, rye and maize are covered along with pulses, legumes, oil seed rape and soybean. Coverage includes principles of production such as pollination, agronomy issues such as site selection and cultivar purity, seed processing, drying and storage. A focus on global food security is maintained throughout.
Keywords: Seed technology